Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Review Exercises - Page 100: 102



Work Step by Step

$$(3x^{4}y^{-2})(-2x^{5}y^{-3})$$ Recall the product rule: $a^{m}⋅a^{n}=a^{m+n}$ Thus, $$(3x^{4}y^{-2})(-2x^{5}y^{-3})$$ $$(3(-2)x^{4+5}y^{-2+(-3)})$$ $$(-6x^{9}y^{-5})$$ Recall the negative exponent rule: $a^{−n}=\frac{1}{a^{n}}$ and $\frac{1}{a^{-n}} = a^{n}$ and the zero exponent rule: $b^{0}=1$ Thus, $$(-6x^{9}y^{-5}) = \frac{-6x^{9}}{y^{5}} = -\frac{6x^{9}}{y^{5}}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.